Big Data from a Student’s Perspective (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Industry Revolution 4.0, or simply “Industry 4.0”, marks the next paradigm shift in mechanized and automized work in a global economy. Digital entities such as the Internet of Things (IoT), Artificial Intelligence and Big Data are one of many building blocks that pave the way for Industry 4.0. As a student, realizing the need to incorporate Industry 4.0 concepts into our curricula and equipping ourselves with the necessary skillsets while working in tandem with higher education institutions is key in being an Industry 4.0 ready graduate. This article brings forward several key competency areas a creative worker should possess, and reviews how big data, a key component under the umbrella term “Industry 4.0” brings value and enhancements to students. Big data can be used to manage students from monitoring their academic involvement to predicting behavioral aspects. Furthermore, big data and among other Industry 4.0 components sees the emergence of a new type of learning environment called learning factories, where Industry 4.0 concepts are fully integrated within the curriculum on a physical, hands-on setting. Ultimately, big data stimulates research collaboration through data sharing and using developed computational tools to disseminate data, enabling primary research to impart higher accuracy data interpretation.